Relevansi etika ilmiah sebagai landasan kejujuran dalam penelitian di era digital - NASTITI, INES KURNIA; PUTRI, IMELDA NIKE KUSUMA; HABIBAH, SALSABILA ZAKIA NUR; RAMADHANI, LAURA HANANDA (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has brought significant changes to scientific research practices, from data collection and information processing to the publication of findings. While these advances offer convenience and efficiency, the digital era also opens up opportunities for ethical violations, such as plagiarism, data manipulation, fabrication of findings, and the dissemination of unverified scientific information. In this context, scientific ethics has become increasingly relevant as a primary foundation for researcher honesty, integrity, and accountability. Scientific ethics is not only concerned with compliance with formal regulations but also emphasizes the moral responsibility of researchers to produce scientific work that is trustworthy and beneficial to society. With the availability of various digital-based tools such as plagiarism detection applications, automated data analysis tools, and online publication platforms, researchers are required to have a higher ethical awareness to avoid being trapped in dishonest research practices, whether intentional or unintentional. This article discusses the urgency of implementing scientific ethics in facing the challenges of the digital era and emphasizes the importance of strengthening research ethics education for students, academics, and practitioners. By consistently understanding and emphasizing the principles of scientific ethics, research honesty can be continuously maintained, so that research results remain valid and make a real contribution to the development of science in this modern era.